A social realist analysis of participation in academic professional development for the integration of digital technologies in higher education - Mistri, Gitanjali Umesh (Rhodes University, Faculty of Education, Centre for Higher Education Research, Teaching and Learning, 2017)
The introduction of digital technologies at the Durban University of Technology (DUT), in keeping with higher education institutions globally, has had a significant impact on the learning environment at the institution. Despite this the anticipated demand for academic professional development (APD) did not materialise at DUT. Using Margaret Archer's Realist Social Theory (1995) this single-institution case study offers a critical examination of cultural, structural and agential conditions that enable and constrain academic professional development (APD) for the integration of digital technologies in teaching"“learning interactions at a higher education institution in South Africa. Archer's (1995) morphogenetic approach enabled an investigation of the interface between the conditions encountered by the academics (at macro, meso and micro levels), in order to theorise about the material, ideational and agential conditions that obtained and which in turn influenced the decision to participate or not participate in the APD programmes. This longitudinal study from 2012 until 2016 traced the APD related changes following the decision to promote the implementation of digital technologies in teaching"“learning interactions as an institutional imperative. The theoretical framework allowed for an examination of the interpretation of the conditions experienced by academics, either as compatible or contradictory to their individual or collective concerns. It further provided an insight into their evaluation of the legitimacy and value of the APD programmes. The study examined the impact of the provision of resources for APD on the nature of the use of digital technologies in teaching"“learning interactions at the site of the case study, the Durban University of Technology in South Africa. The analysis of academic reactions to the changes instituted at both the meso (institutional) and micro (academic professional development) levels revealed that the changes produced conditions that resulted in limited morphogenesis. In particular, it seems that the disruption brought about by the introduction of the technology imperative was accompanied by conditions resulting in further diversification of academic capacities at the institution. This study advances concrete propositions about the conditions that influenced the APD related responses of the academics to the institutionalisation of e-Learning. The research adds to knowledge through insights into the process theory approach to causation, which recognises that structures, mechanisms and events produce unique effects and that the same mechanisms at times produce different events. This study argues that understanding what underlies a certain course of events may enable informed interventions to create better correspondences between APD and the introduction of digital technologies in higher education. Further, this study has generated insights into the importance of taking into consideration the discipline-related knowledge structures in the design and provision of academic development programmes. It is proposed that the incorporation of organising principles of knowledge practices within the academic professional development programme design would earn value and legitimacy for the programme, and promote participation by academics in digital technology-related academic professional development. In summary, the research contributes to an understanding of why it has been that, even with many first order barriers "“ such as digital access and infrastructural limitations "“ reduced, the uptake of digital technologies and participation in related academic professional development programmes by academics in higher education has yet to initiate a move beyond doing what is familiar in a digitally-mediated learning environment.
Keywords: Compensatory education -- South Africa -- Case studies; Education, Higher -- Computer-assisted instruction; Education, Higher -- Effect of technological innovations on -- South Africa; Durban University of Technology